2020
DOI: 10.35848/1882-0786/ab8e0a
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the optimal thermal excitation of bimaterial cantilevers

Abstract: The thermally induced deflection of bimaterial cantilevers was theoretically examined, and an optimal excitation configuration was determined. The optimal heat spot position, resulting in the maximal deflection, was observed at a central location at 0.5-0.6 length for short cantilevers and it shifted backwards the clamped position at 0.4 length for long cantilevers. The calculated values and recent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Detection using high-harmonic frequencies Atomic force microscope (AFM) with the microcantilever as central nowadays is becoming a conventional device in the detection of micro to nano-objects that helps to reveal the physical and chemical properties in nanoscale. [1][2][3][4][5] Several studies have been adopted to enhance the functionality of the cantilever via changing its cross-section materials [6][7][8][9][10] and dimensions [11][12][13][14][15] and revealed that the sensitivity of the cantilever sensor could be enhanced if higher modes of oscillation are used [16][17][18][19] and the quality factor could be increased, especially when functioned in liquids. 20,21) This is explained by the fact that the surface-to-bulk ratio is lower at higher-order modes, which leads to lower air/fluid damping.…”
mentioning
confidence: 99%
“…Detection using high-harmonic frequencies Atomic force microscope (AFM) with the microcantilever as central nowadays is becoming a conventional device in the detection of micro to nano-objects that helps to reveal the physical and chemical properties in nanoscale. [1][2][3][4][5] Several studies have been adopted to enhance the functionality of the cantilever via changing its cross-section materials [6][7][8][9][10] and dimensions [11][12][13][14][15] and revealed that the sensitivity of the cantilever sensor could be enhanced if higher modes of oscillation are used [16][17][18][19] and the quality factor could be increased, especially when functioned in liquids. 20,21) This is explained by the fact that the surface-to-bulk ratio is lower at higher-order modes, which leads to lower air/fluid damping.…”
mentioning
confidence: 99%